A study on job perception of teachers working in State Agricultural Universities in Karnataka State of India - Abdul Sattar Fazely; Mohammad Naser Moain; Rahim Bakhsh Faqiryar (Journal of Economics and Business Letters, 2026)
This study was carried in Three agricultural universities of India to analyze the job perception of teachers and to understand the association between the selected profile characteristics of teachers with their job perception. A total of 180 teachers from University of Agricultural Sciences, Bangalore (90 Nos) and University of Agricultural Sciences, Dharwad (90 Nos) formed the sample of the research study. The results revealed that a majority of UAS (B) teachers (70.00 %) and UAS (D) teachers (68.89 %) were belonging to medium to high level of job perception categories. More number of Professors (40.01%) and Associate Professors (40.00%) were belonging to high level of job perception, while an equal number of Assistant Professors were belonging to low (33.33%), medium (33.33%) and high (33.34%) level of job perception. There was significant difference in the mean job perception score between Professor and Assistant Professor at 5% level. Education, mass media participation, training undergone, achievement motivation, aspiration, competition orientation, scientific orientation, attitude towards organization and awards/recognition received had significant association with the job perception of teachers at 5% level. Whereas, job experience, perceived work load and organizational climate of the teachers had significant association at 1% level with their job perception.